Comparison of early and late intravenous gamma globulin treatment of Kawasaki disease on fever and cardiovascular complications - Iraj Mohammadzadeh; Alireza Nouroozi; Kazem Babazadeh; Hassan Zamani; Rahim Barari-Savadkoohi; Reza Alizadeh-Navaei (Babol University of Medical Sciences, 2016)
Background: Cardiac involvement was the major leading cause of death in patients with Kawasaki and IVIG administration reduces cardiac complications. The objective of this study was to determine the frequency of cardiovascular complications and duration of fever with regard to the time of intravenous immunoglobulin (IVIG) administration of patients with Kawasaki disease. Methods: This follow-up study was done on all patients with Kawasaki disease who were hospitalized at Amirkola Children’s Hospital between 2006 and 2011. Diagnosis of Kawasaki was clinical and included fever more than 5 days with 4 of 5 signs containing mucosal changes, scaling and skin rash, bilateral nonexudative conjunctivitis, cervical lymph adenopathy and edema in lower extremities. After diagnosis of Kawasaki, all patients received standard treatment (intravenous immunoglobulins and aspirin) and undergoing cardiac echocardiography in 2 weeks, 2 months and 6 months. Information including age, sex, sign of diseases, laboratory findings, and cardiac complications in echocardiography were recorded. Results: This study was performed on 100 patients (61 boys and 39 girls) with Kawasaki disease. The mean age of children was 2.8±2.6 years. Cardiac complication rate was 47% at the onset of the disease and had reached to 7% at the end of the sixth month (P=0.000). Distribution of cardiovascular complications in the second week, the second month and the sixth month after treatment was not significantly different according to the start of time of treatment (p>0.05). Duration of fever in patients who received treatment before 10th day (1.5±1.3) did not have significant difference (P=0.78) with patients who received after 10th day (1.6±0.9). Conclusion: Result shows that most of patients (99%) responded to the treatment with IVIG and ASA and cardiovascular complication ratio decreased. There was not significant relationship between duration of fever and time of IVIG treatment initiation.